Misregulation of ER-Golgi Vesicle Transport Induces ER Stress and Affects Seed Vigor and Stress Response - Zhao, Xiaonan; Guo, Xiufen; Tang, Xiaofei; Zhang, Hailong; Wang, Mingjing; Kong, Yun; Zhang, Xiaomeng; Zhao, Zhenjie; Lv, Min; Li, Lixin (Frontiers in Plant Science, 2018)
Seeds of higher plants accumulate numerous storage proteins to use as nitrogen resources for early plant development. Seed storage proteins (SSPs) are synthesized as large precursors on the rough endoplasmic reticulum (ER), and are delivered to protein storage vacuoles (PSVs) via vesicle transport, where they are processed to mature forms. We previously identified an Arabidopsis ER-localized tethering complex, MAG2 complex, which might be involved in Golgi to ER retrograde transport. The MAG2 complex is composed of 4 subunits, MAG2, MIP1, MIP2 and MIP3. Mutants with defective alleles for these subunits accumulated SSP precursors inside the ER lumen. Here, we report that the mag2-1 mip3-1 and mip2-1 mip3-1 double mutant has more serious vesicle transport defects than the mag2-1, mip2-1 and mip3-1 single mutants, since they accumulate more SSP precursors than the corresponding single mutants, and ER stress is more severe than the single mutants. The mag2-1 mip3-1 and mip2-1 mip3-1 double mutants show growth and developmental defects rather than the single mutants. Both single and double mutant seeds are found to have lower protein content and decreased germinating vigor than wild-type seeds. All the mutants are sensitive to abscisic acid (ABA) and salt stress, and exhibit alteration in ABA signaling pathway. Our study clarified that ER-Golgi vesicle transport affects seed vigor through controlling seed protein quality and content, as well as plant response to environmental stress via influencing ABA signaling pathway.